Speech Disorders In Parkinson’S Disease Patients With Mild Form Of Freezing Of Gait - Galáž, Zoltán (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This paper deals with the description of speech disorders present in the mild stage of freezing of gait (FOG) in patients with Parkinson’s disease (PD). Experimental dataset consisted of 48 PD patients and 52 healthy controls (HC). We used freezing of gait questionnaire (FOG-Q) to characterize FOG in PD. Using one-way analysis of variance, we found loosely adducted vocal folds during phonation (p = 0.0027), increased acoustic noise (p = 0.0294), reduced variability of pitch (p = 0.0440), and reduced mobility of articulatory organs (p = 0.0157) significantly statistically different in PD patients in comparison with HC.
Keywords: Parkinson’s disease; hypokinetic dysarthria; freezing of gait; analysis of variance